A Study on Sustainable Development Goals in Foreign Language Teaching Sets - Sallabas, Furkan; Aytan, Talat; Ungan, Suat; Gunes, Gokhan (MDPI, 2026)
Education for Sustainable Development (ESD) plays a vital role in addressing global sustainability changes, and foreign language teaching may contribute to this process. Nevertheless, studies on the incorporation of Sustainable Development Goals (SDGs) in materials related to teaching Turkish as a Foreign Language (TTFL) are limited. This study examines the representation of the 17 SDGs in TTFL textbooks. A qualitative document analysis was conducted on the A1, B1, and C1 levels of the Yeni & Idot;stanbul textbook series across the social, economic, and environmental dimensions of sustainability. The findings indicate a hierarchical distribution of SDG-related content across proficiency levels. At the beginner (A1) level, the social dimension with emphasis on urban integration themes (78.09%) is dominant, while at the advanced (C1) level, the economic dimension becomes more prominent (43.17%). The most striking result is that the environmental dimension remains the weakest area at all levels (A1: 6.67%; B1: 9.95%; C1: 10.93%). Environmental issues primarily appear as contextual vocabulary rather than critical sustainability content. Although the textbooks support socio-economic integration, they show limited alignment with sustainability literacy goals. The findings highlight the need for a more comprehensive integration of environmental sustainability themes in foreign language curricula.
Keywords: sustainable development goals; education for sustainable development; teaching Turkish to foreigners; textbooks; Science & Technology - Other Topics; Environmental Sciences & Ecology